Strategies to Improve Cooperative Efficiency and Performance Through the Integration of Financial Inclusion, Risk Ratios, and Non-Performing Loans - Elfarida Waty, Virgine Untari; Hidayat, Agus Maolana; Rustandi Kartawinata, Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines strategies to improve cooperative efficiency and performance through the integration of financial inclusion (FI), debt-to-income ratio (DTI), loan-to-value ratio (LTV), individual liquidity (LIQ), and non-performing loan (NPL) control. Using data from 705 cooperative members, the research applies multiple linear regression, Sobel mediation test, and PROCESS Model 4 (Hayes, 2022). The results show that financial inclusion significantly reduces NPL (? = -0.401), while both DTI and LTV increase the risk of NPL. NPL acts as a partial mediator in the relationship between financial variables and cooperative performance. The study highlights that financial inclusion is the most significant protective factor against NPL, whereas LTV is the primary risk factor. These findings contribute to the cooperative management literature by providing empirical evidence of the mediating role of NPL and offering strategic recommendations for the sustainable development of cooperatives. By focusing on integrated risk management approaches, cooperatives can improve financial inclusion, reduce NPL risks, and enhance overall performance, ensuring long-term sustainability in the competitive financial landscape. This research underscores the importance of considering both financial inclusion and risk factors when managing cooperatives for improved operational outcomes.